تقويم واقع جودة حياة العمل الدَّاعمة لتطبيق إدارة الجّودة الشَّاملة في المؤسسات التعليمية " دراسة ميدانية على المدارس الثَّانوية الحكومية في مدينة اللاذقية" - زاهر بسام; أبو دولة جمال; زين العابدين دانيا (Latakia University Journal - Economic and Legal Sciences Series, 2013)
اعتمدنا في هذا البحث على تقويم الأبعاد الأساسية الأربعة الآتية لجودة حياة العمل: خصائص الوظيفة, التعويضات, علاقات العمل, ظروف بيئة العمل المادية, للتعرف على مدى ملاءمتها لمتطلبات إدارة الجودة الشاملة. وذلك بالتطبيق على عينة من المدارس الحكومية الثانوية في اللاذقية. ولقد أشارت نتائج البحث إلى: وجود فجوة أو فروق جوهرية في كل من بعدي التعويضات وظروف بيئة العمل المادية , وبأن كلا ً من خصائص الوظيفة وعلاقات العمل تتمتع بالقبول والرضا وفقاً لآراء عينة الدراسة. ولقد قدم البحث مجموعة توصيات منها: ضرورة الاهتمام بسياسة دمج العاملين , وبالإثراء الوظيفي, وكذلك إعادة هيكلة نظام التعويضات بحيث يكون داعماً لإدارة الجودة, وأيضاً ضرورة تعزيز علاقات المودة والتعاون وروح الفريق في بيئة العمل وتدعيمها, وضرورة التطوير المستمر لمكان العمل وتجهيزاته المادية. This research evaluates the following four dimensions of the quality of working life: characteristics of the job, compensation, work relations, the material conditions of the work environment. The aim is to learn about their suitability to the requirements of Total Quality Management. This has been done through applying them on a sample of public secondary schools in Lattakia. The results indicated a gap or statistically significant differences in the dimensions of compensation and the material conditions of the work environment, and that both the characteristics of the job and work relations enjoy acceptance and satisfaction, according to the views of the study sample. The research presented a set of recommendations including: the need to pay attention to the policy of integrating employees, and career enrichment, as well as the restructuring of compensations system so that it becomes supportive of quality management. The research also recommends the need to strengthen relations of affection and cooperation and team spirit in the work environment and enhancing them, and the need for the constant development of workplace & equipment.